2012
DOI: 10.1189/jlb.0212052
|View full text |Cite
|
Sign up to set email alerts
|

A STATus report on DC development

Abstract: DCs have a vital role in the immune system by recognizing exogenous or self-antigens and eliciting appropriate stimulatory or tolerogenic adaptive immune responses. DCs also contribute to human autoimmune disease and, when depleted, to immunodeficiency. Moreover, DCs are being explored for potential use in clinical therapies including cancer treatment. Thus, understanding the molecular mechanisms that regulate DCs is crucial to improving treatments for human immune disease and cancer. DCs constitute a heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 243 publications
(308 reference statements)
1
9
0
Order By: Relevance
“…1B). To examine whether miR-22 is regulated during DC development, we cultured lin − Flt3 + DC progenitors ex vivo with Flt3L or GM-CSF, conditions that promote, respectively, the differentiation of pDCs and cDCs in an approximate 1:1 ratio, or selective cDC differentiation including CD11c + CD11b + B220 − cDCs (reviewed in [25]). We found that miR-22 was highly induced in GM-CSF cultures, while slightly repressed in Flt3L cultures (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). To examine whether miR-22 is regulated during DC development, we cultured lin − Flt3 + DC progenitors ex vivo with Flt3L or GM-CSF, conditions that promote, respectively, the differentiation of pDCs and cDCs in an approximate 1:1 ratio, or selective cDC differentiation including CD11c + CD11b + B220 − cDCs (reviewed in [25]). We found that miR-22 was highly induced in GM-CSF cultures, while slightly repressed in Flt3L cultures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…cDCs have been further subdivided on the basis of tissue localization, cell surface marker protein expression and function. Both cDC and pDC populations arise from common DC progenitors (CDPs, lin − Flt3 + CD115 + CD117 −/lo ) in bone marrow, under control of key cytokines and lineage-restricted transcription factors (reviewed in [24] and [25]). Despite accumulating evidence indicating the important roles of miRNAs in hematopoiesis, little is known about their function in controlling DC development.…”
Section: Introductionmentioning
confidence: 99%
“…). These results suggest a model in which GM‐CSF‐responsive STAT5 and Flt3L‐responsive STAT3 signaling in CDPs influences the expression of the key DC transcriptional regulators Id2 and E2‐2 ( Fig. ).…”
Section: Function Of Stats In DC Subset Diversificationmentioning
confidence: 75%
“…pDCs derive directly from common dendritic precursor cells in the bone marrow in a Flt3L-dependent manner and then travel to lymphoid and nonlymphoid tissues via the blood, rather than entering peripheral tissues as a precursor cell (126,158,231). Development of pDCs has been shown to depend on the transcription factors E2-2 (Tcf4) (40,72) and IRF8 (200,226), among others (122). Comparative microarray studies show that pDCs exhibit similar gene expression profile regardless of their tissue of origin, suggesting that pDCs comprise a single DC subset of common developmental origin (150).…”
Section: Characterizing Vascular Dendritic Cell Subsetsmentioning
confidence: 98%